2011
DOI: 10.1177/0748233711422732
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of rat breast cancer by genistin and selenium

Abstract: Breast cancer is the second leading cause of cancer death among women and the third most common cancer. In this study, we investigated the chemoprevention efficacy of each of soy genistin, selenium or a combination of them against breast cancer. Seventy-five female rats were divided into five groups : control group (I); 7,12-dimethylbenz(a)anthracene (DMBA) group (II); DMBA treated with genistin group (III); DMBA treated with selenium group (IV); and DMBA treated with genistin combined with selenium group (V).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 67 publications
3
10
0
Order By: Relevance
“…These results are consistent with the results which found that serum and tissue lipid peroxidation and NO level were increased significantly in the breast cancer-bearing animals induced by DMBA 9. The present results are also in agreement with many previous reports 52,6266. In consistency with the present study, the results of another study showed that an increase in the MDA level was observed in the lactiferous ducts of rats exposed to DMBA 67.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These results are consistent with the results which found that serum and tissue lipid peroxidation and NO level were increased significantly in the breast cancer-bearing animals induced by DMBA 9. The present results are also in agreement with many previous reports 52,6266. In consistency with the present study, the results of another study showed that an increase in the MDA level was observed in the lactiferous ducts of rats exposed to DMBA 67.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, a substantial decrease in breast GSH content was detected. These results are in accordance with other studies66,93 which revealed that the total antioxidant level was detectably decreased in the serum of DMBA group as compared with the control group. Moreover, the present study is in agreement with Kaufmann et al33 who reported that the enzymic antioxidant SOD, CAT, and GPx levels in cancer-induced animals were reduced when compared to the control animals.…”
Section: Discussionsupporting
confidence: 93%
“…Genistin has attracted much attention due to its wide variety of pharmacological activities, such as weak oestrogen activity [1], antioxidant activity [2,3], hemolysis activity and antibacterial activity [4]. It is also considered as an effectual preventive for breast cancer [5], colon cancer [6], osteoporosis [7] and so on. Therefore, Genistin is often used as dietary supplements [8].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, mammary tissue Se was not lower in TB mice; one possible explanation for this result is that decreased mammary fat pad contents were observed compared with CNL animals. It appears that alterations in Se concentrations occur during cancer development [23]; whereas improved Se status associated with decreased oxidative stress may be useful for preventing the progression of breast cancer [46]. …”
Section: Discussionmentioning
confidence: 99%